2017
DOI: 10.1111/cas.13246
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral bidirectional transitions between epithelial and mesenchymal cells in triple‐negative breast cancer

Abstract: Epithelial–mesenchymal transition (EMT) and its reverse process, mesenchymal–epithelial transition MET, are crucial in several stages of cancer metastasis. Epithelial–mesenchymal transition allows cancer cells to move to proximal blood vessels for intravasation. However, because EMT and MET processes are dynamic, mesenchymal cancer cells are likely to undergo MET transiently and subsequently re‐undergo EMT to restart the metastatic process. Therefore, spatiotemporally coordinated mutual regulation between EMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…CD44 low non-CSC populations, isolated from five different basal breast cancer cell lines, also reported a return to CD44 high state in vivo [66]. The dynamic EMT and MET was also observed in parental and HCC38 cells delineated by EpCAM profiling [26], in Zeb1 driving CD44 Low to CD44 High cellular plasticity [58] and in mammary carcinoma mouse MyPT models delineated by E-cadherin profiling [30]. Autocrine signaling is also speculated to play a significant role in EMP dynamics [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 low non-CSC populations, isolated from five different basal breast cancer cell lines, also reported a return to CD44 high state in vivo [66]. The dynamic EMT and MET was also observed in parental and HCC38 cells delineated by EpCAM profiling [26], in Zeb1 driving CD44 Low to CD44 High cellular plasticity [58] and in mammary carcinoma mouse MyPT models delineated by E-cadherin profiling [30]. Autocrine signaling is also speculated to play a significant role in EMP dynamics [67].…”
Section: Discussionmentioning
confidence: 99%
“…EMP-specific cellular phenotypes can be isolated using EpCAM, Integrin-β4 or CD44/CD24 expression in basal-like cell lines representing TNBC [26,27,28,29], or by using E-cadherin in mammary carcinoma in mouse PyMT models [30]. Similar work has also shown that basal, luminal and stem-like cancer cell subpopulations, isolated from different breast cancer cell lines, can stably retain intra-tumoral heterogeneity, and that all three populations of cells are able to initiate tumor formation in vivo [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that EMT contributes to cancer metastasis by facilitating local invasion, intravasation, transport, extravasation (by allowing cells to move to nearby blood vessels), and finally colonization [ 161 ]. During cancer, EMT and MET show a dynamic relationship in which cells transiently undergo MET and in the next step undergo EMT to restart the metastatic process [ 162 ]. A study by Yamamoto et al showed that spatiotemporally coordinated mutual regulation between EMT and MET could occur during metastasis [ 162 , 163 ].…”
Section: Role Of Emt and Met In Csc Establishment And Progressionmentioning
confidence: 99%
“…During cancer, EMT and MET show a dynamic relationship in which cells transiently undergo MET and in the next step undergo EMT to restart the metastatic process [ 162 ]. A study by Yamamoto et al showed that spatiotemporally coordinated mutual regulation between EMT and MET could occur during metastasis [ 162 , 163 ].
Fig.
…”
Section: Role Of Emt and Met In Csc Establishment And Progressionmentioning
confidence: 99%
“…When cultured, the isolated epithelial and mesenchymal cells remained in their initial cell state, while the E/M hybrid tumour cells exhibited plasticity, transitioning into either epithelial or mesenchymal states within 24 hrs of plating. It has been shown that EMP state subpopulations isolated from systems with inherent EMP tend to revert to a stable equilibrium, as seen with EpCAM-low subpopulations of MMTV-PyMT [Beerling et al, 2016] and PMC42-LA [Bhatia et al, 2019] cells, and either epithelial (EpCAM high ) or mesenchymal (EpCAM low ) subpopulations of the HCC-38 human breast cancer cell line [Yamamoto et al, 2017], all of which revert to a tightly controlled epithelial: mesenchymal ratio [Beerling et al, 2016]. In SCC9 cells, pEMT high and pEMT low subpopulations remained distinct at 4 hours and 24 hours of culture after cell sorting, but resembled parental SCC9 cells after 4 days [Puram et al, 2017].…”
Section: The E/m Hybrid Phenotype In Experimental Systemsmentioning
confidence: 99%